A TWO-STAGE SAMPLE OF A CITY. - Kish, Leslte (American Sociological Review)
This article is a bare description of one way of meeting a particular sampling problem. The reasons for using a probability model are omitted. Within that model there is freedom for a great deal of variety; and that freedom should be used with the aim of selecting those procedures which will meet the study objectives with the greatest accuracy and the greatest economy within the limits of available resources. Here is presented only one set of procedures for meeting the problem but one which will be useful in many situations. In the appendix the reader will find mention of some other procedures, descriptions or definitions of some of the terms; and also some references to more adequate discussions of some of the problems. It is advisable to consult a sampling statistician with the plans before they are put into execution. He may discover possible sources of bias which may have crept into the design. He may suggest ways for improving the efficiency of the design either through more appropriate selection procedures, or through an improved procedure of estimation.